INFLAMMATORY AND MECHANICAL BACK PAIN: AVOIDING DIAGNOSTIC DELAY IN AXIAL SPONDYLOARTHRITIS - Kowalik, Adrianna; Krajewska, Agnieszka; Korzeniewska, Agnieszka Maria; Dębczak, Julia Agnieszka; Łuczak, Karolina; Tłustochowicz, Katarzyna; Korba, Magdalena; Malicka, Natalia; Polkowska, Wiktoria (International Journal of Innovative Technologies in Social Science, 2026)
Background: Low back pain is a common clinical complaint, most often of mechanical origin. However, a subset of patients presents with inflammatory back pain related to axial spondyloarthritis (axSpA), a condition frequently associated with significant diagnostic delay and adverse outcomes. Objective: To review and summarize the key clinical, laboratory, and imaging features that differentiate inflammatory from mechanical back pain, with the aim of improving early recognition of axial spondyloarthritis in clinical practice. Materials and Methods: A narrative literature review was conducted using the PubMed database. Articles published mainly between 2000 and 2024 were identified using the following keywords: “axial spondyloarthritis”, “inflammatory back pain”, “mechanical back pain”, and “diagnostic delay”. Relevant clinical trials, observational studies, systematic reviews, and clinical guidelines written in English were included. The review focused on the epidemiology, clinical presentation, laboratory markers, imaging findings, treatment implications, and prognostic consequences of delayed diagnosis in axial spondyloarthritis, and the selected studies were analyzed qualitatively. Results: Inflammatory back pain is characterized by insidious onset, improvement with exercise, nocturnal pain, and poor response to rest. HLA-B27 positivity and elevated inflammatory markers support the diagnosis, while imaging of the sacroiliac joints—particularly MRI—plays a key role in early detection. In contrast, mechanical back pain is typically activity-related, improves with rest, and rarely shows inflammatory laboratory or imaging findings. Diagnostic delay in axSpA is associated with worse functional outcomes, reduced spinal mobility, and increased radiographic progression. Conclusions: Accurate differentiation between inflammatory and mechanical back pain is essential for timely diagnosis and appropriate management of axial spondyloarthritis. Increased clinical awareness and a structured diagnostic approach may reduce diagnostic delay and improve long-term patient outcomes.